2012
DOI: 10.1270/jsbbs.62.263
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a high-density reference linkage map of tea (<i>Camellia sinensis</i>)

Abstract: A few linkage maps of tea have been constructed using pseudo-testcross theory based on dominant marker systems. However, dominant markers are not suitable as landmark markers across a wide range of materials. Therefore, we developed co-dominant SSR markers from genomic DNA and ESTs and constructed a reference map using these co-dominant markers as landmarks. A population of 54 F1 clones derived from reciprocal crosses between ‘Sayamakaori’ and ‘Kana-Ck17’ was used for the linkage analysis. Maps of both parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…As SSR markers for genotyping, we selected 23 loci from the core map of C. sinensis (Taniguchi et al 2012) to cover the whole genome evenly (Supplementary Tables 2 and 3). Polymerase chain reaction (PCR) was performed in a 10-μL reaction mix including 20 ng of total DNA, 10× PCR Gold buffer (Life Technologies, Carlsbad, CA, USA), 0.8 μL of 8 mM dNTPs, 0.1 U of AmpliTaq Gold polymerase (Life Technologies), 0.8 μL of 25 mM MgCl 2 , and 1 μM of each forward and reverse primer.…”
Section: Dna Extraction and Ssr Marker Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As SSR markers for genotyping, we selected 23 loci from the core map of C. sinensis (Taniguchi et al 2012) to cover the whole genome evenly (Supplementary Tables 2 and 3). Polymerase chain reaction (PCR) was performed in a 10-μL reaction mix including 20 ng of total DNA, 10× PCR Gold buffer (Life Technologies, Carlsbad, CA, USA), 0.8 μL of 8 mM dNTPs, 0.1 U of AmpliTaq Gold polymerase (Life Technologies), 0.8 μL of 25 mM MgCl 2 , and 1 μM of each forward and reverse primer.…”
Section: Dna Extraction and Ssr Marker Analysismentioning
confidence: 99%
“…Polymerase chain reaction (PCR) was performed in a 10-μL reaction mix including 20 ng of total DNA, 10× PCR Gold buffer (Life Technologies, Carlsbad, CA, USA), 0.8 μL of 8 mM dNTPs, 0.1 U of AmpliTaq Gold polymerase (Life Technologies), 0.8 μL of 25 mM MgCl 2 , and 1 μM of each forward and reverse primer. The primer sequences are listed in Taniguchi et al (2012). The PCR reactions were carried out in a GeneAmp 9700 thermal cycler (Life Technologies) according to the following "touchdown PCR" cycling program: 95°C for 5 min, 95°C for 1 min, 62°C for 30 s, and 72°C for 1 min; 13 cycles at annealing temperatures decreasing by 0.5°C per cycle; and 25 cycles of 95°C for 1 min, 55°C for 30 s, and 72°C for 1 min, and a final 72°C for 10 min.…”
Section: Dna Extraction and Ssr Marker Analysismentioning
confidence: 99%
“…The high frequency of SNPs presents high potential for the development of associated genetic mapping studies. For example, Taniguchi et al (2012) reported 3 new reference genetic maps for tea using 1124 markers, including 441 SSRs. The average distances between markers was 1.93 cM [cultivar (cv) 'Sayamakaori'], 1.85 cM (cv 'Kana-Ck17'), and 4.35 cM (core map, constructed by merging the markers present in both parents), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the reference map as a central core map is sandwiched between the parental maps for each linkage group; the combined maps containing 441 SSR, 7 CAPS, 2 STS, and 674 RAPD markers were developed. This newly constructed linkage map can be used as a basic reference linkage map of tea (Taniguchi et al 2007(Taniguchi et al , 2012.…”
Section: Genetic Linkage Mapmentioning
confidence: 99%